Intraspecific morphological variability of Capila pauripunetata Chou & Gu, 1994 (= C. pauripunetata tamdaoensis Devyatkin, 1996 syn. nov.) (Hesperiidae, Pyrginae) - Wang, Zhe; Inayoshi, Yutaka; Saito, Kotaro; Liu, Zhi-Fa; Xue, Guo-Xi (Zootaxa, 2026)
Based on a comparative study on the morphological characteristics of over sixty specimens, Capila pauripunetata tamdaoensis Devyatkin, 1996 syn. nov. is proposed to be a junior subjective synonym of C. pauripunetata Chou & Gu, 1994. Genitalia of both sexes of C. pauripunetata from Hainan are described. Information on the distribution of this species is discussed.